Beyond the Hidden Curriculum: Gender, Textbooks, and Educational Equity - Kencana, Nila; Susanti, Arik (Lingua : Journal of Linguistics and Language, 2025)
This study presents a narrative review of gender representation in language textbooks, examining how male and female characters are depicted across diverse educational and cultural contexts. The review aimed to identify patterns of underrepresentation, role stereotyping, and heteronormativity, as well as to explore how systemic factors shape textbook content. A systematic literature search was conducted in Scopus, Web of Science, and Google Scholar using targeted keywords and Boolean combinations. Inclusion criteria focused on peer-reviewed studies from 2010 to 2025 that analyzed gender representation in language textbooks through content analysis, discourse analysis, or mixed methods. The findings reveal persistent gender imbalances, with men more frequently represented in professional and public domains, while women are marginalized or confined to domestic roles. Cross-national comparisons demonstrate that such disparities are more pronounced in developing countries but also persist globally, including in contexts with progressive policies. Furthermore, heteronormativity remains dominant, with LGBTQ+ identities largely absent from textbook narratives. These outcomes underscore the gap between policy commitments to gender equity and entrenched cultural, political, and religious influences in education. Addressing these challenges requires curricular reforms, stronger enforcement of gender-sensitive guidelines, and teacher training to critically engage with biased materials. Future research should broaden geographic scope, adopt intersectional perspectives, and investigate digital learning environments. By highlighting both persistent inequities and potential avenues for reform, this review emphasizes the importance of inclusive and equitable textbooks in shaping learners’ identities and opportunities.